TANTANGAN PENDIDIKAN ISLAM ABAD XXI - Mardjun, Azma N. (Institut Agama Islam Negeri (IAIN) Palu, 2007)
The development of information of electronics media performs a great role and even determines an individualâs life style. The electronics technologies such as computer, facsimile and internet have changed information milieu from a local milieu to national and international ones. It is within this context that Islamic education must produce human resources not only as information receivers but also as information users who can manage information beneficial to their life skills in facing information globalizationKata Kunci: Pendidikan Islam, abad XXI, golobalisai, media elektronik